2020
DOI: 10.3390/s21010002
|View full text |Cite
|
Sign up to set email alerts
|

Individualised Responsible Artificial Intelligence for Home-Based Rehabilitation

Abstract: Socioeconomic reasons post-COVID-19 demand unsupervised home-based rehabilitation and, specifically, artificial ambient intelligence with individualisation to support engagement and motivation. Artificial intelligence must also comply with accountability, responsibility, and transparency (ART) requirements for wider acceptability. This paper presents such a patient-centric individualised home-based rehabilitation support system. To this end, the Timed Up and Go (TUG) and Five Time Sit To Stand (FTSTS) tests ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 77 publications
0
17
0
1
Order By: Relevance
“…This is evidenced through both the accuracy of the model and the specific misclassifications. The misclassification cases were effectively leading to appropriate actions and thus to a fully trustworthy system, in accordance with the ART principles 24 .…”
Section: Limitationsmentioning
confidence: 92%
See 2 more Smart Citations
“…This is evidenced through both the accuracy of the model and the specific misclassifications. The misclassification cases were effectively leading to appropriate actions and thus to a fully trustworthy system, in accordance with the ART principles 24 .…”
Section: Limitationsmentioning
confidence: 92%
“…Interpretation of the AI output provides a prompt that supports the practitioners' ability to understand what care pathway or treatment/action is suitable for each result in all possible eventualities. There is no further interpretation required by the practitioner to estimate possible misclassification probabilities or errors, enforcing high explainability with no need for transparency in the decision taken by the algorithm, so providing dimensions that translate to accountable reliable and trustworthy (ART) principles 24 .…”
Section: Diagnostic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, the environment and assessment are essential to support engagement and motivation. Thus, Vourganas et al 6 demonstrated a patient‐centric individualized home‐based rehabilitation support system with the help of accountability, responsibility, and transparency (ART) AI. They used the timed up and go (TUG) and five‐time sit to stand (FTSTS) tests to evaluate patients’ daily living activity performance in the presence or development of comorbidities.…”
Section: Telerehabilitation and Remote Assessmentmentioning
confidence: 99%
“…Patients must often continue rehabilitation exercises at home after being discharged. To improve compliance with these exercise programs, patient motivation and involvement need to be strengthened [48]. Resources to assist patients in home rehabilitation are often generic and not well adapted to the individual's needs and preferences [49].…”
Section: Application In Physical and Rehabilitation Medicinementioning
confidence: 99%